Paul, Judaism, and the Gentiles: beyond the new perspective - Watson, Francis (Eerdmans, 2007)
In this new, completely rewritten edition of his major 1986 book, Francis Watson extends, updates, and clarifies his response to E. P. Sanders' view of Paul, in order to point the way beyond the polarization of "new" and "old" perspectives on the apostle. The Paul who comes to light in these pages is agent and thinker, apostle and theologian. He is a highly contextual figure, yet his account of Christian identity continues to shape the church's life to this day. He is the founder of mainly Gentile, Christ-believing communities, separated from the synagogue; and yet he can see this distinctive existence as an authentic response to Jewish scripture and tradition, as fulfilled in Christ. He is a many-sided figure, transcending all our attempts to categorize him or to co-opt him for our own favored causes.